Obstetrical and perinatal consequences of childbirth in women with antenatally undiagnosed fetal growth restriction - Puchkov, V. A.; Pavliuchenko, M. I.; Bohomolova, O. A.; Пучков, Володимир Анатолійович; Павлюченко, Михайло Іванович; Богомолова, Оксана Андріївна (Запорізький державний медико-фармацевтичний університет, 2023)
Aim. Based on a retrospective analysis, assess the obstetric and perinatal consequences of childbirth in women with antenatally undiagnosed fetal growth restriction. Materials and methods. An analysis of 488 cases of childbirth in women with singleton pregnancy, who gave birth to a live child, was conducted. In all cases, the gestational age was ≥22 weeks with a fetal weight less than the 10th percentile for the corresponding gestational age. Depending on the antenatally established diagnosis of FGR, two study groups were formed: group I consisted of 204 (41.8 %) cases with antenatally diagnosed FGR, group II – 284 (58.2 %) cases in which signs of FGR were identified after the birth of the child. Maternal characteristics, neonatal outcomes, and evaluation of short-term infant outcomes were analyzed. Results. Both groups were dominated by women with first births, the number of which was almost the same. Somatic pathology was almost 2 times more common in women of group I, 17.2 %, compared to 9.2 % of women in group II (p < 0.01), this indicates that the majority of women who were not diagnosed with FGR during pregnancy belong to the low-risk group. Fetuses with impaired blood flow in the umbilical cord arteries were twice as common in group I, 49.5 % versus 23.9 % in group II (p < 0.0001), and the frequency of absent/reversible end flow in the umbilical arteries in group I compared to group II, prevailed 3 times (p < 0.0001), indicating more serious lesions of the placenta and, as a result, early manifestation of the fetal condition disorder. The frequency of premature abdominal delivery was 3.75 times higher in group I compared to group II. The most frequent indication for cesarean delivery in both groups was signs of fetal distress syndrome. Analysis of neonatal outcomes showed that the average birth weight was significantly lower in group I and was 2180 ± 55 g against 2420 ± 61 g in group II (p < 0.0001). The need for hospitalization of newborns in the intensive care unit had no statistical difference between the groups (p > 0.05). However, the complications of the early neonatal period and the total length of stay in the hospital were greater in children of the I group, compared to the II group (p < 0.0001). Мета роботи – на підставі ретроспективного аналізу здійснити оцінювання акушерських і перинатальних наслідків розродження жінок з антенатально не діагностованою затримкою росту плода. Матеріали та методи. Проаналізували 488 випадків пологів у жінок з одноплідною вагітністю, які народили живу дитину. В усіх випадках термін вагітності становив ≥22 тижні з масою плода, що менша за 10 перцентиль для відповідного терміну гестації. Залежно від антенатально встановленого діагнозу ЗРП, сформували дві групи дослідження: І – 204 (41,8 %) випадки з антенатально діагностованою ЗРП; ІІ – 284 (58,2 %) випадки, коли ознаки ЗРП ідентифіковано після народження дитини. Вивчили материнські характеристики, неонатальні результати, оцінили короткострокові результати лікування немовлят. Результати. В обох групах переважали жінки з першими пологами, кількість яких в групах зіставна. Соматичну патологію майже вдвічі частіше діагностували в жінок І групи (17,2 %) порівняно з ІІ (9,2 %) (р < 0,01). Це свідчить, що більшість жінок, у яких під час вагітності не було діагностовано ЗРП, належать до групи низького ризику. Порушення кровотоку в артеріях пуповини вдвічі частіше фіксували в плодів І групи (49,5 %) щодо ІІ (23,9 %) (р < 0,0001). Частота нульового / реверсивного кровотоку в артеріях пуповини втричі переважала в І групі порівняно з ІІ (р < 0,0001). Це свідчило про складніші ураження плаценти, а отже й ранню маніфестацію порушення стану плода. Частота дострокового абдомінального розродження в 3,75 раза вища в І групі. Найчастіше показання до кесаревого розтину в обох групах – ознаки дистрес синдрому плода. Аналіз неонатальних наслідків показав: середня маса при народженні вірогідно менша в І групі, становить 2180 ± 55 г, у ІІ – 2420 ± 61 г (р < 0,0001). Не виявили статистично значущої різниці між групами за необхідністю госпіталізації новонароджених у відділення інтенсивної терапії (р > 0,05). Втім, частота ускладнень раннього неонатального періоду та загальна тривалість перебування в стаціонарі більші в дітей І групи порівняно ІІ (р < 0,0001).
Акушерські та перинатальні наслідки пологів у жінок з антенатально не діагностованою затримкою росту плода
Puchkov V. A. - ORCID ID: 0000-0003-4393-5079; Pavliuchenko M. I. - ORCID ID: 0000-0002-9235-0205; Bohomolova O. A. - ORCID ID: 0000-0002-6577-5574.
Keywords: fetal growth restriction; prenatal diagnosis; perinatal consequences; затримка росту плода; пренатальна діагностика; перинатальні наслідки